2010
DOI: 10.3109/00365599.2010.504191
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines, endothelial dysfunction and nutritional status in peritoneal dialysis patients

Abstract: The nutritional status of lean and overweight patients was comparable. Signs of malnutrition were detected in both groups. The severity of chronic inflammation and oxidative stress were not related to BMI in PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
2
6
0
2
Order By: Relevance
“…The metabolic pathway of leptin is through glomerulus filtration, followed by degradation within the renal tubules; thus, a high serum level of leptin is often observed in kidney disease patients (51). Elevated serum leptin levels may cause weight loss, malnutrition and anorexia, which can deteriorate the symptoms of kidney disease patients and are detrimental for the long-term survival of patients (36,52). PD, as a first-choice RRT, uses the peritoneum as a dialysis membrane, and is a safe and gentle method to correct metabolic and electrolytic disturbances generated in kidney diseases, including the clearance of leptin (53).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic pathway of leptin is through glomerulus filtration, followed by degradation within the renal tubules; thus, a high serum level of leptin is often observed in kidney disease patients (51). Elevated serum leptin levels may cause weight loss, malnutrition and anorexia, which can deteriorate the symptoms of kidney disease patients and are detrimental for the long-term survival of patients (36,52). PD, as a first-choice RRT, uses the peritoneum as a dialysis membrane, and is a safe and gentle method to correct metabolic and electrolytic disturbances generated in kidney diseases, including the clearance of leptin (53).…”
Section: Discussionmentioning
confidence: 99%
“…Although both HD and PD have been established and successful therapies for the treatment of patients with end-stage renal disease (ESRD) have been developed, the mortality rate of dialysis subjects remains unacceptably high. Apart from the traditional risk factors, there are the specific non-traditional ones, such as inflammation, oxidative stress, and endothelial dysfunction that seem to be the major culprits (Malgorzewicz et al, 2010). As stated above, they are also strongly associated with PEW.…”
Section: Introductionmentioning
confidence: 98%
“…[15][16][17] There have been few studies of the relationship between adiponectin and the nutritional status of dialysis patients. 18,19 Although one study showed that increased levels of adiponectin are associated with a worse nutritional-inflammatory status in peritoneal dialysis patients, this correlation was not observed in hemodialysis patients. 19 Therefore, we hypothesized that elevated serum adiponectin levels are related to the nutritional status of hemodialysis patients.…”
Section: Introductionmentioning
confidence: 99%